Direcionadores e inibidores para o consumo colaborativo no cenário brasileiro - Freitas, Cláudio Kury (2017)
The act of sharing is as old as the history of humankind. For many years sharing is being studied as a fundamental conduct in the consumption behavior. Nowadays society is experimenting changes provoked by the sharing economy and collaborative consumption. The social media that showed up in the later decade changed the routine of the society and new consuming ways using these virtual platforms invaded the market so that people can buy everything via Internet. Despite the shock caused by this new reality for the worldwide economies, the sharing economy and the collaborative consumption are just in its embryionic state. The studies related to these themes are still scarce not only in the market but in the academy too, exception for specific works through case studies or trying to better understand such a business platform born in this digital era. Thus for the experts perceptions searching about what can make easy or difficult this growing trend becomes relevant also in the Brazilian scenario. Given the above considerations this research has as its objective to analyze the experts perceptions about key drivers and inhibitors in the collaborative consumption in the Brazilian scenario. It was applied the Delphi method and its rankings approach to reach a common understanding among entrepreneurs of collaborative social projects, entrepreneurs of digital platforms and researchers/ academics. As a result of this study it was checked the main key drivers and inhibitors for the collaborative consumption in the Brazilian scenario, regarding sociocultural, technological, economic and political-legal perspectives. It was possible to relate perspectives of drives and inhibitors for the Brazilian collaborative consumption. Also, the research provided a consistent framework to support analyses and future studies about the construct, not well explored yet. Beyond the results, the study contributed for the academy giving a broad vision and knowledge about the literature, recent globally, specially in the Brazilian scenario; contributed with different sectors from the academy, beyond Business Administration; and expanded the knowledge about collaborative consumption from empiric evidences brought by specialists. As contribution for the business, the work increased the comprehension about the collaborative consumption phenomena, and the management vision about future perspectives.